A Systematic Literature Review: The Effect of Health Education Concepts of Cervical Cancer in Community Based - Bando, Epina Felizita; Mohamed Saifulaman Mohamed Said; Tukimin bin Sansuwito; Jipri Suyanto (Public Health of Indonesia, 2025)
Background: Cervical cancer remains a major global public health issue, particularly as a leading cause of mortality among women of reproductive age in low- and middle-income countries. The disease is predominantly associated with infection by the human papillomavirus (HPV). Despite its preventable nature, cervical cancer continues to pose a significant health burden due to limited access to screening and treatment services. Early detection through regular screening, such as Pap smears, and increased awareness of risk factors and early symptoms are critical in reducing morbidity and mortality. However, a key barrier to early detection and prevention is limited health literacy among women. Therefore, there is a pressing need for targeted health promotion and education interventions aimed at enhancing knowledge, awareness, and preventive practices related to cervical cancer. Objectives: This study aims to investigate the impact of health education interventions on the prevention of cervical cancer using a systematic literature review approach. Methods: A systematic search of peer-reviewed literature was conducted using indexed databases, including ScienceDirect, PubMed, and Google Scholar. Studies published between 2019 and 2024 were screened based on relevance to the topic, study design, type of intervention, and reported outcomes. Fourteen studies that met the inclusion criteria were selected for review. Data extraction focused on identifying key findings related to the effectiveness of health education, which were subsequently analyzed using a narrative synthesis approach. Results: Analysis of the included studies revealed that health education interventions have a significant positive impact on knowledge, attitudes, and behaviors related to cervical cancer prevention. Whether implemented through community-based programs, professional healthcare training, or digital platforms, these interventions consistently improved participants’ awareness and engagement in preventive practices. Notably, the integration of traditional educational strategies with innovative technologies, such as mobile health applications, demonstrated enhanced effectiveness in increasing health literacy and participation. Conclusion: Health education represents a fundamental strategy in global efforts to reduce the incidence and mortality of cervical cancer. However, the effectiveness of these interventions varies depending on the population, cultural context, and delivery method. Tailoring educational programs to local needs and incorporating technology may optimize their reach and impact. Keywords: health literacy; awareness; attitude; cervical cancer prevention; health education